Interaction between donor obesity and prolonged donor ischemic time in heart transplantation. Issue 4 (October 2022) - Kim, Samuel T.; Helmers, Mark R.; Iyengar, Amit; Han, Jason J.; Patrick, William L.; Weingarten, Noah; Herbst, D. Alan; Atluri, Pavan
Abstract: Background: The purpose of the study was to determine the impact of donor obesity on outcomes following heart transplantation in the setting of routine (<4 h) and prolonged (≥4 h) organ ischemic times. Methods: Retrospective review of the 2000–2020 United Network for Organ Sharing Database was performed to identify adult heart transplant recipients and donors. Nearest-neighbor propensity score matching by donor obesity was performed separately among routine and prolonged cohorts, with Kaplan-Meier survival estimates used to assess survival at 5 years following transplantation. Results: A total of 43, 304 heart transplant recipients were included in analysis, with 15, 925 (36.8 %) receiving obese donor hearts. After propensity-score matching, 30-day mortality and 5-year survival following transplantation were not statistically different between recipients of obese and non-obese donor hearts when organ ischemic times were routine . In the setting of prolonged organ ischemic times, those receiving obese donor hearts experienced lower 30-day mortality (5.1 % vs 6.7 %, p = 0.04) and improved 5-year survival (74.9 % vs 71.2 %, p < 0.01) compared to non-obese donor hearts. Conclusions: Recipients of obese donor hearts experienced improved outcomes compared to those receiving non-obese donor hearts when organ ischemic times exceeded 4 h. These findings suggest that the detrimental impact of prolonged organ ischemic time may be attenuated by donor obesity. Graphical abstract: Unlabelled Image Highlights: Organ ischemic times in heart transplantation have increased in recent years. Obese donors yielded similar recipient survival when ischemic times were routine. Obese donors yielded higher recipient survival when ischemic times were prolonged. Donor obesity may have cardioprotective effects when ischemic times are prolonged.